2022
DOI: 10.3390/pharmaceutics14102212
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Hypericin to Gold Nanoparticles for Enhancement of Photodynamic Therapy in MCF-7 Breast Cancer Cells

Abstract: Breast cancer, among the different types of cancer, is one of the most diagnosed cancers and the leading cause of mortalities amongst women. Factors, including genetic and epigenetic alterations in tumors, make it resistant to therapies, which results in treatment failures and/or recurrence. Furthermore, the existing therapies have many unfavorable side effects leading to poor prognosis and reduced therapeutic outcomes. Photodynamic therapy (PDT) is one of the most effective cancer therapies with increased sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Apoptotic cell death is linked to direct cell injury when the PS is found in the mitochondria and results in Bcl‐2 damage and Cyt c release (Peng et al, 2022). “One or both of the two primary apoptotic pathways—the Bcl‐2 family of proteins controls the intrinsic pathway and the death domains protein of tumor necrosis factor receptors (TNF‐R) controls the extrinsic pathway—are mediated by caspases” when NE‐PDT is used to induce apoptosis in mammalian cells (Mokoena et al, 2022). Apoptotic genes like Death receptor 5 (DR5), the Fas cell surface death receptor (Fas), and the p53 apoptotic trigger linked to PMP22 start the extrinsic apoptotic pathway (PERP; Merlin, Dellaire, et al, 2021).…”
Section: Apoptotic Signaling Pathways Of Pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptotic cell death is linked to direct cell injury when the PS is found in the mitochondria and results in Bcl‐2 damage and Cyt c release (Peng et al, 2022). “One or both of the two primary apoptotic pathways—the Bcl‐2 family of proteins controls the intrinsic pathway and the death domains protein of tumor necrosis factor receptors (TNF‐R) controls the extrinsic pathway—are mediated by caspases” when NE‐PDT is used to induce apoptosis in mammalian cells (Mokoena et al, 2022). Apoptotic genes like Death receptor 5 (DR5), the Fas cell surface death receptor (Fas), and the p53 apoptotic trigger linked to PMP22 start the extrinsic apoptotic pathway (PERP; Merlin, Dellaire, et al, 2021).…”
Section: Apoptotic Signaling Pathways Of Pdtmentioning
confidence: 99%
“…Quantum dots exhibit unique optical properties for targeted imaging and therapeutic purposes (Han et al, 2019). AUNPs enhance light absorption, improving PDT efficacy (Mokoena et al, 2022). Silica NPs facilitate drug delivery and can be modified for specific targeting, ensuring precise treatment (Sivamaruthi et al, 2023).…”
Section: Types Of Nps Used In Ne-pdtmentioning
confidence: 99%
“…This could enable greater subcellular accumulation (Mkhobongo et al, 2022). Sonication was used to physically adsorb hypericin onto AuNPs, creating a non‐covalent molecule that enhanced the accumulation of drug in MCF‐7 cells to raise the PDT effectiveness between the lower and higher doses (Mokoena et al, 2022).…”
Section: Strategies Based On Nano‐pdtmentioning
confidence: 99%
“…The non-covalent bonds between the AuNPs and Hyp increase the PS accumulation in MCF-7 breast cancer cells and hence improve PDT efficiency with the minimum concentrations. From this study, it is revealed that physically loaded Hyp PS on AuNPs is a hopeful strategy for hydrophobic PS drug delivery to improve PDT efficiency [ 116 ]. The recent studies involving PS-conjugated AuNPs for PDT against cancer using in vitro models are listed in Table 4 .…”
Section: Ps Conjugated Gold Nanocarriers For Pdtmentioning
confidence: 99%